Nurturing Global Synergy Through Education, Culture, And Community Enggagement - Sabariah; Rufii; Adi Bandono; Suhari; Dani (Universitas Veteran Bangun Nusantara, 2026)
ABSTRACT Education plays a strategic role in fostering social cohesion and global synergy through the strengthening of intercultural competencies, dialogue, and cross-community collaboration. However, in practice, challenges remain, including unequal access, low community participation, and the suboptimal integration of local cultural values in learning processes. These conditions may hinder the development of global literacy and sustainable community engagement. This community service program aims to enhance the synergy between education, culture, and society through a participatory approach involving schools, teachers, students, and the wider community. The intervention was implemented through joint needs identification, collaborative planning, culturally based activities (such as outreach sessions, knowledge-sharing forums, and teacher–student collaboration), teacher capacity building, and participatory evaluation. The results indicate an increase in teachers’ and participants’ understanding of global literacy and local cultural values, improved collaborative skills among teachers and university students, and higher active participation of the school community in learning activities. Measurable indicators of achievement include active engagement throughout all program sessions, the establishment of a sustainable collaboration model between the university and the partner school, and the development of a follow-up action plan for program continuation at At-Toyyibah School. This program produces outputs in the form of a locally based collaborative education model, enhanced teacher capacity in global literacy-based learning, and strengthened multi-stakeholder networks that support program sustainability. Overall, the activities contribute to strengthening the synergy between education, culture, and community in promoting inclusive and sustainable global citizenship. Keywords: Inclusive Education, Global Synergy, Community Engagement, Local Culture, Community Empowerment